Preparation method of stretchable color-changing mechanical luminescent fiber

By using microfluidic spinning technology and core-sheath structure design, the problems of continuous and stable molding and color change during strain of silicone-based stretchable mechanoluminescent fibers have been solved, resulting in improved luminescence stability, water resistance, and mechanical properties, as well as enhanced signal output accuracy.

CN121087653APending Publication Date: 2025-12-09BEIJING INST OF CLOTHING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511191664.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve continuous and stable molding of silicone-based stretchable mechanoluminescent fibers, and the fibers cannot change from red to green mechanoluminescence during strain.

Method used

Microfluidic spinning technology is used to set the flow rate ratio of the inner and outer fluids to be greater than 0.35. The PDMS prepolymer of ZnS:Cu and Al2O3 in the inner fluid is configured and a core-sheath structure is formed by dipping. Combined with SASNE particles, a stretchable color-changing mechanoluminescent fiber is formed.

Benefits of technology

It achieves improvements in luminescence stability, water resistance, and mechanical properties, while also improving the accuracy of signal output by changing from red to green mechanical luminescence during strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121087653A_ABST
    Figure CN121087653A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of stretchable color-changing mechanical luminescent fibers, and belongs to the technical field of mechanical stress luminescent fibers. The invention aims to solve the technical problems of high luminous intensity, stability, mechanical property, washing resistance and mechanical luminescence of changing from red to green in a strain process. According to the key points of the technical scheme, the preparation method of the stretchable color-changing mechanical luminescent fiber comprises the following steps: preparing an inner layer fluid, an outer layer fluid and a coagulating bath; spinning by adopting a coaxial needle head and setting the flow rates of fluid in the inner layer and the outer layer to obtain a composite fiber with a skin-core structure, and then heating to complete curing of the inner core layer; the cured composite fiber is soaked in a sodium citrate solution, and Al2O3 (at) ZnS: Cu / PDMS MLF is obtained; the Al2O3 (at) ZnS: Cu / PDMS MLF is immersed in a PDMS / normal hexane solution, then coated with SASNE, heated and cured, and the Al2O3 (at) ZnS: Cu / PDMS MLF is obtained; the inner-layer fluid is a PDMS prepolymer added with ZnS: Cu and Al2O3, the outer-layer fluid is an SA aqueous solution, and the coagulating bath is a CaCl2 aqueous solution; the inner and outer fluid flow velocity ratio is larger than or equal to 0.35.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mechanical stress luminescent fiber technology, and provides a method for preparing stretchable color-changing mechanical luminescent fiber. Background Technology

[0002] For understanding the technical content of this invention: Mechatronic light-emitting fibers (MLFs) are fibers that can directly convert external mechanical energy into light energy under mechanical action, enabling stress visualization without external power supply or light source irradiation. They are typically composed of mechatronic (ML) particles and an elastic polymer matrix. Taking zinc copper sulfide (ZnS:Cu) / polydimethylsiloxane (PDMS) as an example, it has great application potential in the field of smart wearable displays due to its high luminous efficiency, luminous stability, and excellent mechanical properties.

[0003] However, due to the long curing and cross-linking time required for silicone rubber systems, the preparation of silicone-based MLF currently mainly employs a coating method. Because silicone systems have high viscosity and are prone to forming beads, continuous and stable molding is difficult. Furthermore, since the emission color of ZnS:Cu luminescent particles is relatively uniform, the overall MLF intensity is at a low level. This makes it difficult to accurately determine the magnitude of the luminescence intensity under external forces such as stretching, bending, and torsion of the MLF. Therefore, relying solely on changes in brightness or intensity to quantify or semi-quantitatively process mechanical parameters has significant limitations in practical applications.

[0004] Relevant patent documents retrieved: This document, published in China (CN 115726193 B) on March 3, 2023, discloses a method for preparing a fiber matrix liquid by wet milling ZnS:Cu powder and anhydrous ethanol followed by drying; mixing polydimethylsiloxane (PDMS) as the main agent and auxiliary agent in a specific ratio; curing the fiber matrix liquid to obtain PDMS fibers; impregnating and adhering polymethyl methacrylate particles to the cured PDMS fibers to obtain core fibers; adding isopropanol, ZnS:Cu powder, and Al2O3 powder to the fiber matrix liquid to prepare a pressure-emitting layer solution; impregnating and curing this solution to obtain fiber A, which emits green light upon pressure; and adding pretreated ZnS:Cu powder and polytetrafluoroethylene powder to the fiber matrix liquid to prepare a stretching emitting layer solution; impregnating fiber A in the stretching emitting layer solution; and curing this solution to obtain a multiaxial flexible emitting fiber capable of both stretching and pressure-emitting emission. The material prepared by this method only emits green light and cannot change from red to green during strain to exhibit mechanoluminescence.

[0005] This patent, published in China (CN119663477A) on March 21, 2025, discloses a continuous method for preparing strain-luminescent fibers. The method includes preparing a sheath solution and a core solution, with the core solution being a strain-luminescent solution. The sheath solution and core solution are fed into a coaxial wet spinning apparatus to prepare gel fibers with a solidified sheath solution. The gel fibers are then heated to solidify the core solution, yielding strain-luminescent fibers. The patent states that the fibers exhibit bright green light, with higher brightness at faster stretching frequencies. However, the material prepared by this method only emits green light and cannot undergo mechanoluminescence (transitioning from red to green) during straining.

[0006] Relevant non-patent literature retrieved: The journal or book title is "New Chemical Materials," and the document title is "Preparation and Luminescent Properties Study of Zinc Sulfide-Based Mechanoluminescent Powders," Volume 51, Issue 3, Publication Date: March 2023. This document discloses the coating of ZnS:Cu@Al2O3 powder with Al2(SO4)3 and the preparation of an elastomer by combining it with PDMS. However, experimental measurements show that the strongest emission peaks of both photoluminescence and mechanoluminescence of the powder are located around 510 nm, within the green light range. Furthermore, the powder does not exhibit mechanoluminescence, which transitions from red to green during strain.

[0007] The prior art represented by the aforementioned documents has at least the following unresolved technical problems or defects: 1. Continuous and stable molding of silicone-based stretchable mechanoluminescent fibers is difficult to achieve. Relevant evidence includes Chinese patent CN119663477A, ​​which describes strain-luminescent materials primarily using polydimethylsiloxane (PDMS) as the matrix and copper- or manganese-doped zinc sulfide (ZnS:Cu(Mn)) as the luminescent material. The luminescent materials are obtained in elastomer, film, or fiber form through physical mixing / thermal curing, molding, impregnation, and coating methods. However, PDMS lacks spinnability and cannot be formed into fibers independently. Currently, most strain-luminescent fibers are formed by injecting a PDMS / ZnS:Cu mixed solution into an elastic tube and further curing it. However, this results in large fiber diameters, making it difficult to bend and deform significantly, failing to meet the flexibility and comfort requirements of fabrics, exhibiting poor fiber strength, and hindering continuous processing.

[0008] 2. Mechanoluminescence that cannot change from red to green during strain. Relevant evidence includes: "Preparation and Luminescence Performance Study of Zinc Sulfide-based Mechanoluminescent Powder" and patent CN115726193B, both of which emit green light and cannot change from red to green during strain.

[0009] In solving the above problems or overcoming the above defects, the present invention encountered the following difficulties and obstacles: The problem of bubble removal and ZnS:Cu sedimentation in fluid during the microfluidic molding process of silicone-based stretchable mechanoluminescent fibers. Summary of the Invention

[0010] The purpose of this invention is to provide: A method for preparing a stretchable color-changing mechanoluminescent fiber, and related technologies, to solve technical problems such as improving luminescence stability, water washability, mechanical properties, ML strength, and mechanoluminescence that changes from red to green during strain, or combinations thereof.

[0011] Terminology Explanation: Unless otherwise defined, all technical terms in this document have the same meanings as commonly understood by one of ordinary skill in the art to which the subject matter of the claims pertains. Unless otherwise stated, all patents, patent inventions, and publications cited in this document are incorporated herein by reference in their entirety. If multiple definitions exist for terms in this document, the definitions in this chapter shall prevail.

[0012] It should be understood that the above brief description and the following detailed description are exemplary and for illustrative purposes only, and do not limit the subject matter of the invention in any way. In this invention, the singular is used in conjunction with the plural unless otherwise specifically stated. It should also be noted that, unless otherwise stated, the use of “or” or “or” means “and / or”. Furthermore, the use of the term “comprising” and other forms such as “including,” “containing,” and “contains” are not limiting.

[0013] The definition of the standard chemical term can be found in the reference "Advanced Textile Composites: Beijing: China Textile Press Co., Ltd.: October 2020: 1st Edition."

[0014] Unless otherwise stated, conventional methods within the scope of the art, such as SEM measurement, measurement of the number of excited photons during ML, mechanical property testing, luminescence stability testing, and water washability testing, shall be used.

[0015] Unless specifically defined herein, the use of all commercially available products herein employs standard techniques. For example, it may be carried out using the manufacturer's instructions for use with the kit, or in accordance with methods known in the art or the description of this invention. The techniques and methods described herein can generally be implemented according to conventional methods well known in the art, based on the descriptions in the various summary and more specific documents cited and discussed in this specification.

[0016] The term "core-sheath structure" used in this article refers to a structure in which the morphological structure of some natural fibers and nascent fibers obtained by wet spinning has radial differences.

[0017] The term "dip coating" as used in this article refers to a coating process, primarily used to form a coating by immersing tools in a solution after liquefying polymer materials.

[0018] In a first aspect, the present invention provides a method for preparing a stretchable, color-changing, mechanoluminescent fiber, comprising the following steps: (1) Configure the inner fluid, outer fluid and coagulation bath; (2) Using a microfluidic spinning needle, the inner fluid velocity and the outer fluid velocity are set to spin fibers. (3) The obtained fiber was heated and then soaked in sodium citrate solution to obtain Al2O3@ZnS:Cu / PDMSMLF; (4) Immerse Al2O3@ZnS:Cu / PDMS MLF in PDMS / n-hexane solution, coat with SASNE, and heat to cure to obtain the product; The inner fluid is a PDMS prepolymer with added ZnS:Cu and Al2O3, the outer fluid is an aqueous SA solution, and the coagulation bath is an aqueous CaCl2 solution. The ratio of the inner fluid velocity to the outer fluid velocity is greater than or equal to 0.35.

[0019] Among them are technical features such as ZnS:Cu, Al2O3, SA aqueous solution, CaCl2 aqueous solution, PDMS / n-hexane solution, etc.

[0020] Among them, the mass fraction of ZnS:Cu in the inner fluid is selected from 25-60%.

[0021] The preferred mass fraction of ZnS:Cu in the inner fluid is 45-60%.

[0022] The preferred feature is that the mass fraction of ZnS:Cu in the inner fluid is 55-60%.

[0023] The preferred mass fraction of ZnS:Cu in the inner fluid is 55%, 56%, 57%, 58%, 59%, or 60%.

[0024] The mass ratio of Al2O3 to ZnS:Cu is selected from 0 to 0.2:1.

[0025] The preferred mass ratio of Al2O3 to ZnS:Cu is 0.05-0.2:1.

[0026] The preferred mass ratio of Al2O3 to ZnS:Cu is 0.05-0.15:1.

[0027] The preferred mass ratio of Al2O3 to ZnS:Cu is 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, or 0.15:1.

[0028] The mass concentration of the SA aqueous solution is selected from 0.2-5 wt%.

[0029] The preferred mass concentration of the SA aqueous solution is 1.5-3 wt%.

[0030] The preferred mass concentration of the SA aqueous solution is 1.5-2 wt%.

[0031] The preferred mass concentration of the SA aqueous solution is: 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%.

[0032] The mass concentration of the CaCl2 aqueous solution is selected from 2-4 wt%.

[0033] The preferred mass concentration of the CaCl2 aqueous solution is 2.5-4 wt%.

[0034] The preferred technical feature is that the mass concentration of the CaCl2 aqueous solution is 2.5-3 wt%.

[0035] The preferred mass concentrations of the CaCl2 aqueous solution are: 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, and 3 wt%.

[0036] The dosage of the technical feature SASNE is selected from 0.05-0.3 g / m.

[0037] The preferred dosage of the technical feature SASNE is 0.1-0.2 g / m.

[0038] The preferred dosage of the technical feature SASNE is 0.1-0.15 g / m.

[0039] The preferred dosage of the technical feature SASNE is: 0.1 g / m, 0.11 g / m, 0.12 g / m, 0.13 g / m, 0.14 g / m, and 0.15 g / m.

[0040] Based on further solutions to the technical problems of the present invention, or simultaneous solutions to multiple technical problems, the preferred solution in the technical solution provided in the first aspect of the present invention includes: The first preferred solution is the mass fraction of ZnS:Cu in the inner fluid. This technical solution, based on solving the technical problem of "improving luminescence stability, water washability, mechanical properties, and ML strength", further solves the technical problem of "further improving luminescence stability, water washability, mechanical properties, and ML strength".

[0041] The second preferred option is the mass ratio of Al2O3 to ZnS:Cu. This technical solution, having already addressed the technical issues of "improved luminescence stability, water washability, mechanical properties, and ML strength," further addresses the technical issue of "further improved luminescence stability, water washability, mechanical properties, and ML strength."

[0042] The third preferred option: the dosage of SASNE. This technical solution, based on solving the technical problem of "mechanical luminescence that changes from red to green during strain", further solves the technical problem of "more sensitive mechanical luminescence that cannot change from red to green during strain".

[0043] Secondly, the present invention provides: a stretchable color-changing mechanoluminescent fiber prepared by the aforementioned preparation method.

[0044] Thirdly, the present invention provides: the application of a stretchable color-changing mechanoluminescent fiber in the preparation of functional smart textiles.

[0045] This includes technical features such as functional smart textiles.

[0046] Among them, the technical features and functions of smart textiles are selected from: smart sports vests, smart wound dressings, smart sportswear, smart sports shoes, implantable devices, smart display fabrics, interactive textiles, etc.

[0047] Fourthly, the present invention provides: a functional smart textile comprising the above-mentioned stretchable color-changing mechanoluminescent fiber.

[0048] Embodiments 1-2 of this invention at least support the protection scope of claim 1.

[0049] Regarding the claim 1: The technical feature “the ratio of inner fluid velocity to outer fluid velocity is greater than 0.5” is defined by the foregoing explanation and / or the corresponding technical feature Q in Examples 1-2. in / Q outThe values ​​of 0.35-0.8 are generalized from the common feature "greater than or equal to 0.35". Therefore, those skilled in the art can reasonably infer that the technical feature of the ratio of inner fluid velocity to outer fluid velocity being greater than or equal to 0.35, the subordinate concept of the ratio of inner fluid velocity to outer fluid velocity being greater than or equal to 0.35, the technical means that are basically equivalent to the ratio of inner fluid velocity to outer fluid velocity being greater than or equal to 0.35, and the technical means that can replace the ratio of inner fluid velocity to outer fluid velocity being greater than or equal to 0.35 based on the existing technical level and common knowledge, should all fall within the protection scope of claim 1. For example, if other technical features remain unchanged, replacing the ratio of inner fluid velocity to outer fluid velocity being greater than or equal to 0.35 with the ratio of outer fluid velocity to inner fluid velocity being less than 2.86, it still falls within the protection scope of claim 1 of this invention.

[0050] Embodiments 1-2 of this invention at least support the protection scope of claim 2.

[0051] The technical feature “ZnS:Cu mass fraction in the inner fluid is 25-60%” is derived from the aforementioned explanation and / or the corresponding technical feature x=0.25-0.6 (mass fraction 25-60%) in Examples 1-2, and is summarized by the common feature “ZnS:Cu mass fraction in the inner fluid”. Therefore, those skilled in the art can reasonably infer that the technical feature ZnS:Cu mass fraction in the inner fluid, the subordinate concept of ZnS:Cu mass fraction in the inner fluid, the technical means that are basically equivalent to ZnS:Cu mass fraction in the inner fluid, and the technical means that can replace the ZnS:Cu mass fraction in the inner fluid based on the existing level of technology and conventional technical means and common knowledge, should all fall within the protection scope of claim 2.

[0052] Embodiments 1-2 of this invention at least support the protection scope of claim 3.

[0053] The technical feature “mass ratio of Al2O3 to ZnS:Cu 0-0.2:1” is derived from the aforementioned explanation and / or the corresponding technical feature y=0-0.2 (mass ratio 0-0.2:1) in Examples 1-2, and is summarized from the common feature “mass ratio of Al2O3 to ZnS:Cu”. Therefore, those skilled in the art can reasonably infer that the technical feature of mass ratio of Al2O3 to ZnS:Cu, the subordinate concept of mass ratio of Al2O3 to ZnS:Cu, the technical means that are basically equivalent to mass ratio of Al2O3 to ZnS:Cu, and the technical means that can replace mass ratio of Al2O3 to ZnS:Cu based on the existing technical level within the scope of conventional technical means and common knowledge should all fall within the protection scope of claim 3. For example, replacing mass ratio of Al2O3 to ZnS:Cu with 0.21:1 while keeping other technical features unchanged still falls within the protection scope of claim 3 of this invention.

[0054] The beneficial effects of this invention are as follows: The present invention has at least the following beneficial effects: Compared with existing technologies, the present invention has better technical effects in terms of luminescence stability, water washability, mechanical properties, ML intensity, and mechanoluminescence that changes from red to green during strain.

[0055] According to experimental tests, the present invention enables mechanical luminescence that changes from red to green during strain, which is impossible to achieve with existing technology.

[0056] Furthermore, based on the present invention: Based on the comparison of Examples 1-2 and Comparative Examples 1-4, the present invention employs a combination of technical means, such as an inner layer fluid velocity to outer layer fluid velocity ratio greater than 0.5 and a specific fiber diameter, to achieve new technical effects, improving luminescence stability, washability, mechanical properties, ML strength, and mechanoluminescence that changes from red to green during strain. The combined technical effect is superior to the sum of the effects of each individual technical means. Attached Figure Description

[0057] Figure 1 The light intensity is the light emission intensity during the ML process in Example 1.

[0058] Figure 2 The luminescence intensity is shown in the ML process of Example 2.

[0059] Figure 3 The luminescence intensity during the ML process of fibers with different diameters.

[0060] Figure 4The images shown are SEM images of the x=0.5, y=0.1 group in Example 1: (ac) cross-sectional SEM image; (de) side-view SEM image; (fi) EDS energy dispersive spectra of Al, S, Zn, and Ca.

[0061] Figure 5 The image shows the SEM image of the x=0.5, y=0.1 group in Example 1 under stretched conditions.

[0062] Figure 6 The mechanical property test results for the group with x=0.5 and y=0.1 in Example 1 are shown in Figure 1. a is the stress-strain curve and b is the tensile recovery curve.

[0063] Figure 7 The results are the luminescence stability test results for the group with x=0.5 and y=0.1 in Example 1.

[0064] Figure 8 The results are the water washability test results for the group with x=0.5 and y=0.1 in Example 1.

[0065] Figure 9 The morphological changes of fibers under different flow rates.

[0066] Figure 10 This is a diagram illustrating the color transition mechanism of MLF.

[0067] Figure 11 The images show the emission of MLF under different strains in the x=0.5, y=0.1 group of Example 1.

[0068] Figure 12 The images show the MLF spectra of the x=0.5, y=0.1 group in Example 1 under different strains.

[0069] Figure 13 The image shows the colorimetric diagrams of the MLF in Example 1 with x=0.5 and y=0.1 under different strains. Detailed Implementation

[0070] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the invention in any way. The following content is merely an exemplary description of the scope of protection claimed by the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, and such changes should also fall within the scope of protection claimed by the present invention.

[0071] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all instruments, devices, equipment, reagents, products, etc., used in the embodiments of the present invention are obtained through conventional commercial means.

[0072] Example 1 PDMS was purchased from Dow Chemical Company.

[0073] The inner fluid is a PDMS prepolymer with added ZnS:Cu luminescent particles and Al2O3 nanoparticles (the amount of curing agent added is 1 / 10 of the PDMS prepolymer), denoted as ZC. x A y / PDMS dispersion.

[0074] Where ZC represents ZnS:Cu luminescent particles, A represents Al2O3 nanoparticles, x represents the mass fraction of ZnS:Cu in the inner fluid, and y represents the mass ratio of Al2O3 to ZnS:Cu.

[0075] Where y = 0.1; x are 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, and 0.6 respectively.

[0076] The outer fluid is a 1.5 wt% aqueous solution of SA (sodium alginate).

[0077] The coagulation bath was a 2.5 wt% aqueous solution of CaCl2.

[0078] Example 2 The inner fluid is a PDMS prepolymer with added ZnS:Cu luminescent particles and Al2O3 nanoparticles (the amount of curing agent added is 1 / 10 of the PDMS prepolymer), denoted as ZC. x A y / PDMS dispersion.

[0079] Where ZC represents ZnS:Cu luminescent particles, A represents Al2O3 nanoparticles, x represents the mass fraction of ZnS:Cu in the inner fluid, and y represents the mass ratio of Al2O3 to ZnS:Cu.

[0080] Where x = 0.55; y are 0, 0.05, 0.1, 0.15, and 0.2 respectively.

[0081] The outer fluid is a 1.5 wt% aqueous solution of SA.

[0082] The coagulation bath was a 2.5 wt% aqueous solution of CaCl2.

[0083] Preparation method: (1) Preparation of spinning solution: ZnS:Cu luminescent particles and Al2O3 nanoparticles were added to PDMS (the amount of curing agent added was 1 / 10 of the PDMS prepolymer), and mixed evenly to obtain ZnS:Cu luminescent particles and Al2O3 nanoparticles. x A y / PDMS dispersion. After the dispersion was prepared, it was subjected to sonication for 10 min and vacuum degassing for 60 min to eliminate internal suspended air bubbles. Prepare 1.5 wt% SA solution, 2.5 wt% CaCl2 solution and 2 wt% sodium citrate solution.

[0084] (2) Microfluidic molding preparation of Al2O3@ZnS:Cu / PDMS MLF: Conical capillaries were prepared using a capillary needle drawing apparatus and coaxially assembled through a T-shaped tee connector to obtain a microfluidic spinning needle. ZnS was then used to prepare the microfluidic spinning needle. x A y PDMS dispersion, SA solution, and CaCl2 solution were used as the inner layer fluid, outer layer fluid, and coagulation bath, respectively. Appropriate flow rates for the inner and outer layer fluids, as well as suitable extrusion speeds (0-15 ml / h) and collection speeds (approximately 50 cm / min), were set for spinning. The resulting fibers were then transferred to a water bath at 90°C for heating until the PDMS was completely cured. The fibers were then transferred to a sodium citrate solution and immersed for 6 hours to dissolve the outer layer of calcium alginate hydrogel, yielding Al2O3@ZnS:Cu / PDMS MLF stretchable mechanoluminescent fibers.

[0085] The parameters for Examples 1-2 are shown in Table 1.

[0086] Table 1

[0087] Q in Table 1 out =10 mL / h.

[0088] Comparative Example 1 The composition and preparation method are the same as in Example 1, only Q is changed. in / Q ou The parameters are shown in Table 2.

[0089] Table 2

[0090] Q in Table 2 out =10 mL / h.

[0091] Q in / Q out Examination of spinning continuity: Experimental Example 1 The composition and preparation method are the same as in Example 1, except that the flow rates of the inner and outer fluids are changed.

[0092] Q out When the flow rate is 15 mL / h, Q inThey are 1 mL / h, 2 mL / h, 3 mL / h, 4 mL / h, 5 mL / h, 5.5 mL / h, 6 mL / h, 6.5 mL / h, 7 mL / h, 7.5 mL / h, 8 mL / h, 9 mL / h, and 10 mL / h.

[0093] Experiment Example 2 The composition and preparation method are the same as in Example 1, except that the flow rates of the inner and outer fluids are changed.

[0094] Q out When the flow rate is 10 mL / h, Q in They are 1 mL / h, 2 mL / h, 3 mL / h, 3.5 mL / h, 4 mL / h, 4.5 mL / h, 5 mL / h, 5.5 mL / h, 6 mL / h, 7 mL / h, 8 mL / h, 9 mL / h, and 10 mL / h.

[0095] Experimental Example 3 The composition and preparation method are the same as in Example 1, except that the flow rates of the inner and outer fluids are changed.

[0096] Q out When the flow rate is 5 mL / h, Q in They are 1 mL / h, 1.5 mL / h, 2 mL / h, 2.5 mL / h, 3 mL / h, 4 mL / h, 5 mL / h, 6 mL / h, 7 mL / h, 8 mL / h, 9 mL / h, and 10 mL / h.

[0097] The inner fluid, outer fluid, and coagulation bath in Experiments 1-3 were the same as those in Example 1 with x=0.55 and y=0.1.

[0098] The experimental results of Examples 1-3 are shown in [the table]. Figure 9 .

[0099] Application example: Al2O3@ZnS:Cu / PDMS-SASNE / PDMS core-skin structure SASNE source: Raysun Optical Materials ((Sr,Ca)AlSiN3:Eu, wavelength 620nm).

[0100] Preparation of Al2O3@ZnS:Cu / PDMS-SASNE / PDMS core-skin structure MLF by dip coating: First, prepare a 20 wt% PDMS (curing agent added at 1 / 10 of the PDMS prepolymer) n-hexane solution. Immerse the Al2O3@ZnS:Cu / PDMS MLF in the PDMS solution to form a uniform coating on its surface. Then, dip red photoluminescent particles SASNE are coated onto the surface. Heat and cure at 90℃ for one hour. After the PDMS is completely cured, continue to dip and cure the PDMS solution to form a PDMS protective layer to prevent the SASNE luminescent particles from falling off. This completes the preparation of Al2O3@ZnS:Cu / PDMS-SASNE / PDMS core-skin structure MLF.

[0101] The dosage of SASNE in Examples 1-2 and Comparative Examples 1-4 is shown in Table 3.

[0102] Table 3

[0103] Detection Example 1 1. Luminous intensity during the ML process The tensile strain (5-40%) and tensile frequency (5 Hz) of the fixed fiber were subjected to cyclic stretching; photons were collected using a fiber optic spectrometer with an integration time of 5 s and a collection interval of 10 ms; the test was conducted in a dark environment.

[0104] 2. SEM observation of microstructure The surface and cross-sectional morphology of MLF were characterized using scanning electron microscopy.

[0105] 3. Mechanical performance testing (1) Fix the MLF on the tensile testing machine fixture, cut the initial length to 4 cm, set the tensile speed to 50 mm / min, and test to obtain the stress-strain curve.

[0106] (2) Cyclic tensile properties: The strain magnitude is fixed at 60%, the tensile recovery speed is set at 50 mm / min, and the number of cycles is 200.

[0107] 4. Luminescence stability test The tensile strain (40%) and tensile frequency (5 Hz) of the fixed fiber were subjected to 2000 cycles of tensile testing; the ML spectrum was measured every 5 s using a fiber optic spectrometer; the test was conducted in a dark environment.

[0108] 5. Water wash resistance test Simulated washing conditions were employed, with each wash performed by stirring at 40°C for 30 minutes; ML spectra were measured after each wash; and the tests were conducted in a dark environment.

[0109] Verification of technical effectiveness and / or analysis of technical problem solving 1. Luminous intensity during the ML process The test results of Example 1 are shown below. Figure 1 The test results for Example 2 are shown below. Figure 2 , Test results for fibers of different diameters are shown below. Figure 3 .

[0110] 2. SEM observation of microstructure The SEM images for the x=0.5, y=0.1 group in Example 1 are shown below. Figure 4 Al2O3 and ZnS:Cu are uniformly dispersed in the core matrix, while SASNE particles are concentrated in the cortex.

[0111] The SEM images of the group with x=0.5 and y=0.1 under tensile conditions in Example 1 are shown below. Figure 5 .

[0112] The fibers can be bent, knotted, and stretched, exhibiting good flexibility.

[0113] 3. Mechanical performance testing The mechanical property test results for the group with x=0.5 and y=0.1 in Example 1 are shown below. Figure 6 .

[0114] MLF possesses excellent mechanical properties.

[0115] 4. Luminescence stability test The luminescence stability test results for the group with x=0.5 and y=0.1 in Example 1 are shown below. Figure 7 .

[0116] 5. Water wash resistance test The water wash resistance test results for the group with x=0.5 and y=0.1 in Example 1 are shown below. Figure 8 .

[0117] Figure 5 The image shown is an SEM image of MLF under tension, which clearly shows the formation of cracks, confirming this conclusion.

[0118] like Figure 6 The core layer serves as the primary mechanical support layer, providing MLFs with excellent mechanical properties.

[0119] like Figure 7-8 The product of this invention has excellent luminescence stability and water washability.

[0120] Examples 1-3 show the morphological changes of fibers at different flow rates. Figure 9 When the inner and outer layer flow rates are equal to Q in / Q outWhen Q is greater than 0.35, spinning can proceed normally. Preferably, Q... in / Q out When the value is greater than 0.5, the fiber morphology is uniform.

[0121] Due to the dense distribution of SASNE particles in the cortex, under low strain and stretching, the green light emitted by the core layer is low in intensity and is almost completely absorbed by the PL particles and converted into red light. However, as the strain increases, due to the thin cortex (only about 20 μm), cracks gradually form between the particles, and the green fluorescence intensity emitted by the core layer increases, reducing the ability to convert green light into red light. Therefore, MLF gradually shifts to emitting predominantly green light (e.g., ...). Figure 10 (As shown).

[0122] Figure 11 The image shown is an actual emission image of the MLF. It can be clearly seen that the color of the MLF changes from dark red to bright green under different strains. This demonstrates that the accuracy of signal output is improved by coordinating the emission intensity of the MLF with color changes.

[0123] The luminescence properties of MLF under different strains were characterized, with the peak area ratio R of green and red light used to measure their respective contributions. When the tensile strain was 5%, the fiber emitted almost only red light with a wavelength of approximately 620 nm, and the R value was only 0.03. With increasing strain, the red light intensity increased slowly, while the green light intensity increased significantly, and the R value gradually increased to 0.36, 0.96, and 1.63, reaching 2.25 at 40% strain (e.g., ...). Figure 12 As shown in the diagram, as the MLF strain increases from 5% to 40%, the chromaticity diagram coordinates change from (0.65, 0.37) to (0.34, 0.51), transitioning from red to orange-red, orange, yellow, yellow-green, and green, spanning multiple color patches, resulting in significant color differences (e.g., ...). Figure 13 (As shown).

[0124] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a stretchable, color-changing, mechanoluminescent fiber, characterized in that, Includes the following steps: (1) Configure the inner fluid, outer fluid and coagulation bath; (2) Using a microfluidic spinning needle, the inner fluid velocity and the outer fluid velocity are set to spin fibers. (3) The obtained fiber was heated and then soaked in sodium citrate solution to obtain Al2O3@ZnS:Cu / PDMS MLF; (4) Immerse Al2O3@ZnS:Cu / PDMS MLF in PDMS / n-hexane solution, coat with SASNE, and heat to cure to obtain the product; The inner fluid is a PDMS prepolymer with added ZnS:Cu and Al2O3, the outer fluid is an aqueous SA solution, and the coagulation bath is an aqueous CaCl2 solution. The ratio of the inner fluid velocity to the outer fluid velocity is greater than or equal to 0.

35.

2. The preparation method according to claim 1, characterized in that, The mass fraction of ZnS:Cu in the inner fluid is 25-60%.

3. The preparation method according to claim 1, characterized in that, The mass ratio of Al2O3 to ZnS:Cu is 0-0.2:

1.

4. The preparation method according to claim 1, characterized in that, The mass concentration of SA aqueous solution is 0.2-5 wt%.

5. The preparation method according to claim 1, characterized in that, The mass concentration of the CaCl2 aqueous solution is 2-4 wt%.

6. The preparation method according to claim 1, characterized in that, The amount of SASNE applied is 0.05-0.3 g / m.

7. The stretchable color-changing mechanoluminescent fiber prepared by the preparation method according to any one of claims 1-6.

8. The application of the stretchable color-changing mechanoluminescent fiber prepared by the preparation method according to any one of claims 1-6 and / or the stretchable color-changing mechanoluminescent fiber according to claim 7 in the preparation of functional smart textiles.

9. A functional smart textile, characterized in that, Includes the stretchable color-changing mechanoluminescent fiber prepared by the preparation method according to any one of claims 1-6 and / or the stretchable color-changing mechanoluminescent fiber according to claim 7.

10. The functional smart textile according to claim 9, characterized in that, This includes smart sports vests, smart wound dressings, smart sportswear, smart sports shoes, implantable devices, smart display fabrics, and interactive textiles.

Citation Information

Patent Citations

  • A method for preparing a multi-axis flexible luminous fiber capable of stretching and pressing to emit light

    CN115726193B

  • Continuous preparation method of strain luminescent fiber

    CN119663477A